A role for locus coeruleus in Parkinson tremor - Isaias, Ioannis Ugo; Marzegan, Alberto; Pezzoli, Gianni; Marotta, Giorgio; Canesi, Margherita; Volkmann, Jens; Biella, Gabriele E.; Cavallari, Paolo (Frontiers in Human Neuroscience, 2012)
We analyzed rest tremor, one of the aetiologically most elusive hallmarks of Parkinson disease (PD), in 12 consecutive PD patients during a specific task activating the locus coeruleus (LC) to investigate a putative role of noradrenaline (NA) in tremor generation and suppression. Clinical diagnosis was confirmed in all subjects by reduced dopamine reuptake transporter (DAT) binding values investigated by single photon computed tomography imaging (SPECT) with ([123I] N-ω-fluoropropyl-2β-carbomethoxy-3β-(4-iodophenyl) tropane (FP-CIT). The intensity of tremor (i.e. the power of EMG signals), but not its frequency, significantly increased during the task. In six subjects, tremor appeared selectively during the task. In a second part of the study, we retrospectively reviewed SPECT with FP-CIT data and confirmed the lack of correlation between dopaminergic loss and tremor by comparing DAT binding values of 82 PD subjects with bilateral tremor (n=27), unilateral tremor (n=22) and no tremor (n=33). This study suggests a role of the LC in Parkinson tremor.